Effect of Twin Date Events on Online Implusive Buying of Shopee Users in Surabaya - Giovanni, Erik Hardian; Hartini, Sri (SEIKO : Journal of Management & Business, 2023)
E-commerce is a form of buying and selling business that uses the internet network for online purchases. With e-commerce, the buying and selling process becomes easier because it does not require a lot of physical energy and allows more efficient use of time. This study aimed to analyze the effect of the Twin Dates Event on Online Impulsive Buying for Shopee users in Surabaya. This type of research is causality with a quantitative approach. 105 Shopee users in Surabaya were taken as samples in this study using a purposive sampling technique. Hypothesis testing uses the Partial Least Square (PLS) analysis technique. The research findings concluded that the Twin Dates Event has a significant effect on Online Impulsive Buying, so the more interesting the Twin Dates event takes place, the more it can increase impulsive buying online, which then has an impact on increasing the number of purchases on e-commerce Shopee.